Breast Cancer: Coping with Hair Loss - Martha Monroe; Barbara Shea (EDIS)
There are so many things to pay attention to when faced with cancer and chemotherapy that many women may not take the time to look at the bright side of losing their hair. In an attempt to help ease this transition and make light of this inevitable change, this fact sheet has a list of advantages of not having hair. Perhaps you’ll be able to add to this list. Written by Martha Monroe and Barbara Shea, and published by the UF Department of Family Youth and Community Sciences, January 2012.